Biowaste to treasure: Application of microbial-aged hydrochar in rice paddy could improve nitrogen use efficiency and rice grain free amino acids. (10th December 2019) - Yu, Shan; Feng, Yanfang; Xue, Lihong; Sun, Haijun; Han, Lanfang; Yang, Linzhang; Sun, Qingye; Chu, Qingnan
Abstract: Hydrochar is produced under hydrothermal carbonization, which can be considered as a cleaner process for black carbon production. Hydrochar shows good prospects in agro-environmental applications, but it is recommended to be ameliorated before application to improve its surface characteristics and reduce potential side-effects. This study, for the first time, proposed ameliorating poplar sawdust hydrochar via a microbial-aging process and applying it to rice paddy soil. In a soil-column experiment, sawdust hydrochar (SHC), microbial-aged SHC (M-SHC), and water-washed SHC (W-SHC) were added at different rates to examine their effects on rice growth and nitrogen usage efficiency (NUE). Additionally, the effects of hydrochar application on rice grain free amino acids (FAAs) were investigated. The study revealed that M-SHC had a positive effect on rice growth and increased the grain yield by 17.13%–22.99% compared with control. The NUE was also improved by M-SHC treatment. The positive effect of M-SHC on rice yield might be attributed to the reduced toxic biochar-derived dissolved organic matters, increased specific surface area, elevated hydrochar pH, and more nutrients released due to the microbial-aging process. Moreover, under M-SHC treatment, all 17 FAAs of grain were significantly higher than the control, by 46.26%. Both microbial-aging and water-washing amelioration of hydrochar had a positive effect on rice yield and FAAs, with the former exhibiting better prospects for application. This study will provide a new direction for cleaner recycling and utilization of biowaste. Graphical abstract: Image 1 Highlights: Hydrochar was aged by the microbial process in a fermentation system for the first time. Microbial-aged sawdust hydrochar (M-SHC) was applied to rice paddy soils at different rates. M-SHC significantly promoted rice grain yield by 17.13%–22.99%; NUE also improved. M-SHC significantly increased rice 17 free amino acids (FAAs) content by 46.26% at best. M-SHC had neutral pH, more nutrients, less toxic compounds and higher porosity.